Mitochondria-acting nanomicelles for destruction of cancer cells via excessive mitophagy/autophagy-driven lethal energy depletion and phototherapy. (February 2020) - Zhu, Ya-Xuan; Jia, Hao-Ran; Gao, Ge; Pan, Guang-Yu; Jiang, Yao-Wen; Li, Penglin; Zhou, Ningxuan; Li, Chengcheng; She, Cong; Ulrich, Nathan W.; Chen, Zhan; Wu, Fu-Gen
Abstract: Mitophagy is a specific self-protective autophagic process that degrades damaged or dysfunctional mitochondria, and is generally considered to reduce the effectiveness of mitochondria-targeted therapies. Here, we report an energy depletion-based anticancer strategy by selectively activating excessive mitophagy in cancer cells. We fabricate a type of mitochondria-targeting nanomicelles via the self-assembly of D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) and dc-IR825 (a near-infrared cyanine dye and a photothermal agent). The TPGS/dc-IR825 nanomicelles enable mitochondrial damage in cancer cells, which, for self-protection, activate two autophagic pathways, (1) mitophagy and (2) adenosine triphosphate (ATP) shortage-triggered autophagy. However, the excessive mitophagy/autophagy activities far surpass the degradative capacity of autolysosomes, leading to the formation of micrometer-sized vacuoles and degradation blockage. Immunofluorescence staining and Western blot analysis reveal that the nanomicelle-treated cancer cells are under severe ATP shortage, which eventually causes substantial cell death. Moreover, the nanomicelles intravenously injected into tumor-bearing mice show high tumor accumulation, long tumor retention, and inhibit the tumor growth by inducing excessive mitophagy/autophagy and energy depletion in tumor cells. Additional near-infrared laser irradiation treatment further enhances the in vitro and in vivo anticancer efficiencies of the nanomicelles, due to the excellent photothermal and photodynamic effects of dc-IR825. We believe that this work highlights the important role of mitophagy/autophagy in treating cancers. Graphical abstract: Image 1